Tinjauan Psikologi Hukum Terhadap Kematangan Emosi, Kontrol Diri dan Perilaku Agresif pada Anggota Polri dalam Menangani Huru Hara - Nur, Andi Wahyuddin; Yustiana; Hendra Sudrajat; Baso Muhammad Harisah; Andi Astrid Baradillah; Sudarwin (Legal Journal of Law, 2025)
This study aims to determine the emotional maturity, self-control, and aggressive behavior of Polri members in handling riots; and to determine the factors that influence emotions, self-control, and aggressive behavior of Polri members in handling riots. The study was conducted at the Wajo Police. Data collection methods used were interviews and library research. Data were analyzed qualitatively using deductive and inductive methods and then presented descriptively. Data in the form of direct interviews with related parties and in the form of legal products and reading materials related to the object of study to sharpen and deepen the qualitative analysis. The results of the study indicate that emotional maturity and self-control are important factors in shaping the behavior of Polri members who are professional and have integrity, especially when facing riot situations. By improving these two aspects, it is hoped that Polri members can carry out their duties more effectively, maintain security and order, and minimize the negative impact of aggressive behavior; and The factors that influence emotions, self-control, and aggressive behavior of Polri members in handling riots are very complex and diverse. Some internal factors include age, temperament, emotional maturity, and self-esteem. External factors include past experiences, social support, the work environment, and task pressure. Furthermore, conditions such as sleep deprivation, stress, and a lack of understanding of the task can also trigger emotional instability and aggressive behavior